Investigation and Analysis on Employment of Chinese Undergraduate Graduates - Wang Wei; Shang Yixin (Randwick International of Education and Linguistics Science Journal, 2022)
This paper sorts out the data in the employment quality report of colleges and universities, and studies the employment structure, employment choice and reasons of graduates under the first round of "double-first-class" construction policy. It is found that the employment quality of "double-first-class" colleges reflects a higher level, and students' sense of social responsibility is more fully cultivated, which guides graduates to work in key areas and fields.